Mycoplasma Genitalium Infection Prevalence in Patients with Human Immunodeficiency Virus - Rini Rasianti; Hartati Dharmadji; Risa Miliawati; Diah Puspitosari; Feilicia Henrica Teja; Rasmia Rowawi; Rahmatdinata Rahmatdinata; Tony Djajakusumah (Faculty of Medicine Universitas Padjadjaran, 2014)
Objective: To determine the prevalence of Mycoplasma genitalium (M. genitalium) infection in HIV positive patients by PCR examination in Teratai Clinic of Dr. Hasan Sadikin General Hospital, Bandung in order to reduce sexually transmitted diseases, especially M. genitalium infection in HIV positive patients.Methods: This study was a cross-sectional study with consecutive sampling methods. Eighty one HIV positive patients attending the Teratai Clinic of Dr. Hasan Sadikin General Hospital, Bandung were recruited to be the subjects of this study. All subjects underwent history taking, physical examination, and PCR examination for M. genitalium. Specimens were taken from cervical smear in females and first void urine in male.Results: The prevalence of M. genitalium based on the PCR examination in HIV positive patients attended to Teratai Clinic Dr. Hasan Sadikin General Hospital Bandung was 9%. Conclusions: Mycoplasmal infection identification based on PCR examination should be considered for routine screening test to reduce the incidence of sexually transmitted diseases in HIV positive patients.Keywords: Human immunodeficiency virus, Mycoplama genitalium, polymerase chain reaction DOI: 10.15850/ijihs.v2n1.274